Changes in thrombin-stimulated platelet malondialdehyde production during the menstrual cycle. Issue 6 (June 1981) - Tindall, H; Zuzel, M; Paton, R C; McNicol, G P
Abstract : Forty normal women had thrombin-stimulated platelet malondialdehyde (MDA) production measured during their menstrual cycle. Twenty women in this group were taking the combined oral contraceptive pill (OCP). Platelet MDA production was found to fall by 30% during normal menstruation and the week when the subjects were not taking a combined OCP, but it remained constant throughout the remainder of the cycle. No significant change in initial platelet aggregation response to stimulation by thrombin, change in plasma thrombin clotting time, plasma heparin neutralising activity (HNA), or plasma antithrombin III (AT-III) activity was seen when the platelet MDA production was reduced. The bleeding time results showed some variation throughout the menstrual cycle but these did not appear to be related to the variation in platelet MDA production.